Clinical Analysis of Peripheral Vascular Diseade in Patients with Diabetes Mellitus - Malla, Dipak; Dhakal, Sukesh Purush (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Introduction: Diabetes Mellitus (DM) is clinical syndrome characterized by hyperglycemia due to absolute or relative deficiency of insulin. The metabolic dysregulation associated with DM causes multitude of secondary pathophysiological changes in multiple organ system causing macro vascular (coronary artery disease, peripheral vascular disease, cerebrovascular disease) and micro vascular (retinopathy, neuropathy, and nephropathy) complications. This study aimed to study the prevalence of peripheral vascular disease in patients with diabetic mellitus presenting to this tertiary care centre.Methods: This clinical study was conducted in first affiliated hospital of Yangtze university, Jingzhou. All patients with a diagnosis of diabetic mellitus who came to Out patient department of Endocrinology & diabetic clinic and admitted in the hospital during a period between October 2013 to October 2014, who fulfill, were enrolled for the study. This was a single centered retrospective observational analylitcal study conducted in Department of Endocrinology of First affiliated Hospital of Yangtze, China.Results: Peripheral vascular disease was found in 35% of patients studied . There was significant correlation.Conclusion: A significant number of diabetics presenting with diabetes mellitus have underlying peripheral vascular disease. The patients might not all be symptomatic or show obvious signs of PVD but need to be investigated for the same. The older the individual the more the chances of having peripheral vascular compromise. Also a tobacco user and patient presenting with worse clinical findings is more likely to have PVD. Thus the detection of peripheral vascular disease in patients using Arterial Doppler studies along with routine clinical and laboratory assessment can be of great value in long term care of these individualsith age, and history of tobacco use.